Agro-financing, Institutions and Poverty in Low-Middle Income African Countries - Ajayi, Daniel; Osabohien, Romanus A.; Mohammed, Baba Abdullahi; Fagbola, Lawrence Olusegun; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2023)
The study examined the impact of institutions and agro-financing on poverty reduction in Africa's low- and middle-income countries. Pooled OLS analysis and Random effects method were applied to the data sourced from World Development Indicators (WDI), Food and Agriculture Organization (FAO), Africa Country Policy and Institutional Assessment (CPIA) from 2005 to 2020. Consequently, the study found that institutions, agricultural land, agriculture credit are negatively significant to poverty in low and middle-income African countries. In addition, it showed that technology is negatively significant to poverty reduction in low and middle-income African countries. Other variables included in the model – agricultural employment and crop production. The study concludes that the policymakers in low-middle income African countries should embark on development of quality institutions and proper financing of the agricultural sector in order to bring about reduction of poverty in those countries.